Effectiveness of Mindfulness and Qigong Training for Self-Healing in patients with Hwabyung and depressive disorder: a randomized controlled trial - Yoon, Seok-In; Park, Hui-Yeong; Park, Chan; Pyun, Jiho; Yoo, Jae-Hong; Song, Geum-Ju; Lee, Hyun Woo; Chung, Sun-Yong; Kim, Jong Woo (Frontiers in Psychiatry, 2025)
BackgroundHwabyung is a Korean culture-bound syndrome characterized by anger-related physical and psychological symptoms. Depressive disorder is a common mental disorder that occurs worldwide and is highly comorbid with Hwabyung. In traditional East Asian medicine, both Hwabyung and depression are associated with an imbalance in vital energy termed qi. Mindfulness induces psychosomatic balance, and qigong facilitates the cultivation and regulation of qi, which may be effective treatments for Hwabyung and depression. This study aimed to investigate whether Mindfulness and Qigong Training for Self-Healing (MQT-SH) could improve psychosomatic symptoms in patients with Hwabyung and depressive disorders.MethodsThis was a two-arm, randomized controlled trial. Patients diagnosed with both Hwabyung and depressive disorder were included in the trial. A total of 64 participants were recruited and randomly assigned to either the experimental (n=32) or control group (n=32). The experimental group underwent MQT-SH that consisted of mindfulness and qigong for the first six weeks, whereas the control group received no treatment. During the next six weeks, the control group performed MQT-SH for ethical equity. Assessments were conducted at baseline, post-intervention (6-week), and follow-up (12-week).ResultsMQT-SH significantly decreased Hwabyung, depression, anxiety, and anger while increasing subjective vitality, and the effectiveness of the intervention were maintained at a short-term follow-up of 6 weeks. Physical vitality mediated the effectiveness of the MQT-SH on Hwabyung, whereas psychological vitality mediated the effectiveness of the MQT-SH on depression. Only one adverse event was reported during the intervention period. Home practice was not significantly associated with any intervention change.DiscussionThis study demonstrated that MQT-SH is an effective and safe intervention for patients with Hwabyung and depressive disorders. This study explored the possibility that subjective vitality may serve as a mechanism for treating psychosomatic and mood symptoms. Future studies should control for placebo effects and conduct long-term follow-ups.Ethics and disseminationThis study was approved by the Institutional Review Board of Kyung-Hee University Oriental Medicine Hospital in Gangdong (KHNMCOH 2023-09-003).Clinical trial registrationhttps://cris.nih.go.kr/cris/search/detailSearch.do?seq=26882&status=5&seq_group=25511&search_page=M, identifier KCT0008937.